Therapeutic efficacy of praziquantel against trematode infection in one-stripe spiny eel Macrognathus aral - Bera, Asit Kumar; Das, Nilemesh; Manna, Sanjib Kumar; Bhattacharya., Shreya; Sinha, Archana; Das, Basanta Kumar (Journal of the Inland Fisheries Society of India, 2021)
Therapeutic efficacy of praziquantel against trematode infection in one-stripe spiny eel Macrognathus aral